The Coracohumeral Ligament and Its Fascicles: An Anatomic Study - Emilio González-Arnay; Isabel Pérez-Santos; Camino Braojos-Rodríguez; Artimes García-Parra; Elena Bañón-Boulet; Noé Liria-Martín; Lidia Real-Yanes; Mario Fajardo-Pérez (Journal of Functional Morphology and Kinesiology)
Background: The coracohumeral ligament (CHL) is inserted in the coracoid process, from which it extends laterally and caudally, blending with the tendinous insertions of the subscapularis muscle and the supraspinatus muscle, with a third intermediate area between the muscles inserted between the humeral tubercles, and it contributes to the fibrous tunnel that engulfs the long head of the biceps tendon. Most previous studies mention insertions from the base of the coracoid process, but not from the tip, and some authors describe anterior and posterior columns. In contrast, others stress the existence of superficial and deep fascicles. Also, the relationship between the coracohumeral and the glenohumeral ligaments is unclear. Given the position of the CHL covering most of the rotator interval, and its role in the stability of the shoulder capsule and pathologies like frozen shoulder, a clear description of its fascicles in a plane-wise manner might be helpful for a selective surgical approach. Methods: We studied sixteen soft-embalmed shoulders to avoid misclassifying fascicles due to formalin-linked tissue amalgamation. Further histological assessment was performed on the two remaining non-embalmed shoulders. Results: In our sample, the coracohumeral ligament hung from the anterior and posterior edges of the coracoid process’ inferior surface, defining two columns that converged near the tip of the coracoid process. Both columns were formed by superficial and deep fascicles directed to different depths of the rotator cuff, usually via the rotator interval, fusing with the connective tissue around the muscles without direct distal attachments. We performed histological and morphometrical assessments, and we discuss clinical and biomechanical implications. Conclusions: The coracohumeral ligament contains four fascicles that fuse with the connective tissue of the shoulder joint, forming a double necklace around the subscapularis and supraspinatus. Therefore, its functions probably extend beyond simple vertical stabilization.